Using contingent valuation to assess the prospects for local participation in public good provision: The case of trypanosomiasis control in Ethiopia - Swallow, B.M. (International Livestock Research Institute, 2004)
This study is conducted with a general objective of evaluating contingent valuation as a method for assessing the willingness of people at a site in the Ghibe Valley of Ethiopia to contribute labour, time and money to tsetse control. The more specific objectives of the case study were to evaluate the breadth of local support for tsetse control; to determine the acceptability of different mechanisms for enhancing local participation in the finance and operation of the tsetse control programme; and to identify groups likely to play leadership roles or be obstacles to proposed control programmes. Topics of discussion include African animal trypanosomiasis and its control; and factors affecting willingness to contribute. The paper also looks into the contingent valuation method and research design.